Journalism in Time of Pandemic: New Professional Routines, New Ethical Challenges - Miranda, João (2021)
The covid-19 pandemic and the subsequent process of confinement led to lines of convulsion in different sectors of society. Marked by a context of instability and uncertainty, where different manifestations of technological, economic and social transformation enhance new practices and conventions, as well as raising new and renewed deontological challenges, journalism is no exception. Based on the responses of a survey answered by 890 Portuguese journalists, this article seeks to map the effects of the March–April 2020 state of emergency on practices and routines, and on the ethical-professional precepts of an activity that calls for a revived relevance in an environment of disinformation and “infodemic”. More than revealing new problems, the results obtained suggest the intensification of the pre-existing challenges and dilemmas. In terms of practices, it is indicated that the activity is relatively domiciled. This phenomenon is accompanied by marks of depersonalization of contact with sources and events, and by signs of social isolation from journalists. In the ethical-deontological field, the emergence of particular deontological issues in the context of the pandemic, where aspects related to rigour — rejection of sensationalism, a clear distinction between facts and opinion or repudiation of any form of censorship — as well as to subsequent elements underlying contact with the sources, take on a special dimension.